Exploration of Entrepreneurship Education by Linear Regression and Psychological Factor Analysis - Mu, Ke; Shi, Qin; Ma, Yonghong; Tan, Jiao (Frontiers in Psychology, 2020)
To study the improvement of the entrepreneurial performance of start-ups and achieve an organic combination of entrepreneurship education and entrepreneurial performance, the entrepreneurial group of college students was taken as the springboard to discuss the entrepreneurial performance of start-ups initiated by college students. First, through questionnaire design and scale selection, the results of the questionnaire survey and the reliability and validity of the scale tool were tested. Second, the variable of college students’ entrepreneurial self-efficacy based on psychological factor analysis was introduced. The correlations among entrepreneurship education, entrepreneurial self-efficacy, and entrepreneurial performance were analyzed. Finally, the intermediary role of entrepreneurial self-efficacy was verified by using the hierarchical linear regression analysis method combined with the BARON three-part verification method. The results show that the response rate of the questionnaire is 92%, and the selection of research samples is scientific. The Cronbach’s α reliability coefficients corresponding to each scale are all above 0.8, and the common factor variances are all above 0.7. Therefore, the reliability and validity of scale tools are good. Entrepreneurship education, entrepreneurial self-efficacy, and entrepreneurial performance are significantly correlated with each other. The college students’ entrepreneurial self-efficacy has a good explanatory ability and plays an intermediary role; in the entrepreneurial innovation learning dimension, its corresponding β = 0.257; in the dimension of school organizational support, the corresponding β = 0.439; in the dimension of social interaction, the corresponding β = 0.238. The results have a reference value for studying entrepreneurship education and the improvement of entrepreneurial performance from a psychological level.